Detection of water absorption in the day side atmosphere of HD 189733 b using ground-based high-resolution spectroscopy at 3.2 μm★ - Birkby, JL; de Kok, RJ; Brogi, M; de Mooij, EJW; Schwarz, H; Albrecht, S; Snellen, IAG (Oxford University Press (OUP), 2013)
We report a 4.8σ detection of water absorption features in the day side spectrum of the hot Jupiter HD 189733 b. We used high-resolution (R ∼ 100 000) spectra taken at 3.2 μm with CRIRES on the VLT to trace the radial-velocity shift of the water features in the planet's day side atmosphere during 5 h of its 2.2 d orbit as it approached secondary eclipse. Despite considerable telluric contamination in this wavelength regime, we detect the signal within our uncertainties at the expected combination of systemic velocity (⁠Vsys=−3+5−6 km s−1) and planet orbital velocity (⁠Kp=154+14−10 km s−1), and determine a H2O line contrast ratio of (1.3 ± 0.2) × 10−3 with respect to the stellar continuum. We find no evidence of significant absorption or emission from other carbon-bearing molecules, such as methane, although we do note a marginal increase in the significance of our detection to 5.1σ with the inclusion of carbon dioxide in our template spectrum. This result demonstrates that ground-based, high-resolution spectroscopy is suited to finding not just simple molecules like CO, but also to more complex molecules like H2O even in highly telluric contaminated regions of the Earth's transmission spectrum. It is a powerful tool that can be used for conducting an immediate census of the carbon- and oxygen-bearing molecules in the atmospheres of giant planets, and will potentially allow the formation and migration history of these planets to be constrained by the measurement of their atmospheric C/O ratios.